Pengaruh Influencer, Citra Merek Dan Kualitas Produk Bagi Pembelian Kosmetik Wardah Di Kota Bandung - Nayla Kanaya Gunawan; Agus Maolana (Relasi : Jurnal Ekonomi, 2024)
Currently, the use of cosmetics has become a necessity for women and they are used in everyday activities. In the face of intense competition, companies must try hard to market the products they produce by continuously trying to be creative and produce new innovations. Wardah is a very popular brand in the market and is recognized as the first adopter of halal cosmetics in Indonesia. This is research that aims to evaluate how influencers, brand image, and product quality have an impact on purchasing decisions for Wardah Cosmetics products in the Bandung city area. The study uses nonprobability sampling, particularly purposive sampling, and sends questionnaires to 200 participants. Quantitative methods were used in this research. Descriptive and analytical various linear regressions are used in data analysis. The study results show that factors influence buyers' choices, brand image influences buyers' choices, and product quality has a significant influence on buyers' decision-making processes. Keywords: Influencer, Brand Image, Product Quality, Purchasing